The cross-cultural impact of the ingenuine smiling celebrity in online advertising - Broeder,Peter (2019)
Promoting products via Instagram is a rapidly growing phenomenon in the world of online advertising. Standing out with these advertisements and obtaining desired consumer outcomes becomes increasingly challenging due to the enormous amount of advertisements that already have been implemented on this platform. One strategy that could be used is celebrity endorsement, which is a tactic that is - considering celebrities credible and attractive characteristics - proven to be effective for creating favourable attitudes and higher purchase intentions. The present study investigated the effect of an (in)genuine smiling celebrity on consumer behaviour in an Instagram advertisement. Specifically, this study addressed differences between consumers from two cultures: the Netherlands and Spain. An online experiment with two conditions was conducted (ingenuine vs. genuine smiling celebrity). There were 174 Dutch and 137 Spanish participants. The results revealed that smile type did affect consumers purchase intention. Attitudes towards the celebrity influenced the effect of smile type on purchase intention. Cultural background did play a moderating role.